Phalaenopsis is one of the most interesting genera of orchids due to the members are often used as parents to produce hybrids. The establishment and development of highly reliable and discriminatory methods for identifying species and cultivars has become increasingly more important to plant breeders and members of the nursery industry. The aim of this research was to develop sequence-based microsatellite (eSSR) markers for the Phalaenopsis orchid designed from the sequence of GenBank NCBI. Seve - . FATIMAH; DEWI SUKMA (HAYATI Journal of Biosciences, 2011)
Phalaenopsis is one of the most interesting genera of orchids due to the members are often used as parents to produce hybrids. The establishment and development of highly reliable and discriminatory methods for identifying species and cultivars has become increasingly more important to plant breeders and members of the nursery industry. The aim of this research was to develop sequence-based microsatellite (eSSR) markers for the Phalaenopsis orchid designed from the sequence of GenBank NCBI. Seventeen primers were designed and thirteen primers pairs could amplify the DNA giving the expected PCR product with polymorphism. A total of 51 alleles, with an average of 3 alleles per locus and polymorphism information content (PIC) values at 0.674, were detected at the 16 SSR loci. Therefore, these markers could be used for identification of the Phalaenopsis orchid used in this study. Genetic similarity and principle coordinate analysis identified five major groups of Phalaenopsis sp. the first group consisted of P. amabilis, P. fuscata, P. javanica, and P. zebrine. The second group consisted of P. amabilis, P. amboinensis, P. bellina, P. floresens, and P. mannii. The third group consisted of P. bellina, P. cornucervi, P. cornucervi, P. violaceae sumatra, P. modesta. The forth group consisted of P. cornucervi and P. lueddemanniana, and the fifth group was P. amboinensis.